Influence of Forest Combustible Material on the Characteristics and Conditions of Ignition of Bio-coal Water Fuels. Issue 3 (17th February 2023) - Kuznetsov, G.V.; Malyshev, D. Yu; Syrodoy, S.V.; Gutareva, N. Yu; Kostoreva, Zh.A.
ABSTRACT: The results of the experimental studies of the particles ignition of bio-coal water fuels have been presented. The experiments have been carried out on the setup providing an error level of not more than 6.1% of the main recorded characteristics. The effect of the temperature of the oxidizing agent and the characteristic size of the fuel drops on the duration of the induction period of the fuel compositions has been studied. It has been established that the introduction of the additives from forest combustible materials of three typical tree species leads to an acceleration of the ignition process of substantially flooded particles of bio-coal water fuels. According to the results of a detailed analysis of the frames of the videogram, it has been shown that the duration of the intensive chemical reaction of the gaseous pyrolysis products with a high-temperature oxidizer is not more than 0.02% of the entire induction period. Colloquium . One of the possible promising directions for the development of the coal technologies in the energy sector and for reducing the negative anthropogenic impact of the thermal power plants that burn coal is the use of the composite fuels (coal- water (CWF), organ coal- water, etc.) based on coal. But a number of the technological problems significantly complicate the use of such fuels in the energy sector. This is evidenced by a significant increase (over the past 10 years) in the number of the publications devoted to the problems of carbonic fuels. The ignition process of CWF is quite long (ignition delay time (tign ) up to 20 seconds). The use of fuel with such a large induction period in a real practice is practically impossible. One of the possible options for reducing the tign value of the liquid composite fuels is the introduction of biomass into their composition. This is a new composite bio-coal water fuel (Bio-CWF). At present, there are practically no publications devoted to the experimental and theoretical studies of the ignition of Bio -CWF particles under conditions corresponding to the furnaces of the typical boiler units of the thermal power plants. The duration of the characteristic stages of ignition of Bio-CWF particles (made on the basis of coal, water and various types of biomass) is an important characteristic necessary for carrying out the experimental design works on the development of new innovative boiler units burning bio-coal water fuel.